2008
DOI: 10.1530/eje-08-0468
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from thyroid cancer in patients with hyperthyroidism: the Theagenion Cancer Hospital experience

Abstract: Background: Thyroid carcinoma has been reported in patients operated for different types of hyperthyroidism and the probability of a hot nodule being malignant seems to be low. The aim of the present study was to explore the relationship between thyroid cancer, hyperthyroidism and outcome in a large cohort of patients who presented to a tertiary cancer centre in Northern Greece. Patients: Among 720 patients treated for thyroid cancer, 60 had a concomitant diagnosis of hyperthyroidism due to Graves' disease (nZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 29 publications
4
40
1
6
Order By: Relevance
“…For thyroid cancer, previous studies have reported inconsistent results (Cole, 1991;Majima et al, 2005;Pazaitou-Panayiotou et al, 2008). We found increased risks, confined to the early overall Cancer risk after Graves' disease X Shu et al follow-up period, though for men the risk was noted even for the All1 þ period.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…For thyroid cancer, previous studies have reported inconsistent results (Cole, 1991;Majima et al, 2005;Pazaitou-Panayiotou et al, 2008). We found increased risks, confined to the early overall Cancer risk after Graves' disease X Shu et al follow-up period, though for men the risk was noted even for the All1 þ period.…”
Section: Discussioncontrasting
confidence: 54%
“…Inconsistent associations between GD and malignant tumours have been reported (Cristofanilli et al, 2005;Majima et al, 2005;Pazaitou-Panayiotou et al, 2008). Small study size and variable case reporting weaken the generalisability of the results (Majima et al, 2005;Pazaitou-Panayiotou et al, 2008). In our cohort study, the largest to date, 18 156 hospitalised GD patients were studied to quantify their subsequent cancer risk.…”
mentioning
confidence: 89%
“…In many cases thyroid cancer is not known preoperatively, but is found incidentally during postoperative histologic examination of the thyroid [ 33 ] . We previously reported a study of 60 hyperthyroid patients diagnosed with thyroid cancer [ 11 ] . Among those patients, only 12 were operated for suspicion of thyroid cancer preoperatively, whereas in the remaining 48, in whom the indication for thyroidectomy was treatment for thyrotoxicosis, thyroid cancer was incidentally found after surgery.…”
Section: ▼ Thyroid Cancer In Patients With Hyperthyroidismmentioning
confidence: 99%
“…Consequently, FNAB is not recommended (4). Nevertheless, malignancy may be found in AFTNs with non-negligible frequency in both adults and children (5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%